PENENTUAN KUALITAS PERAIRAN SUNGAI SIAK (HULU) DESA BENCAH KELUBI KECAMATAN TAPUNG KABUPATEN KAMPAR BERDASARKAN STRUKTUR KOMUNITAS PLANKTON - Yandriadi Yandriadi; Eni Sumiarsih; Muhammad Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTAlong the watershed of the Siak River, many anthropogenic activities produce pollutant that enter the water and thus decrease the quallity of the water in that river. To understand the water quality of the river based on plankton community, a study has been conducted in December 2019. Samplings were conducted 3 times, in 3 sampling points, once/ week. The plankton were then identified and counted. Results shown that there were 40 species on phytoplankton presence, they were consisted of 6 classes, namely Bacillariophyceae (11 species), Clorophyceae (19 species), Cyanophyceae          (7 species), Dinophyceae (1 species), euglenophyceae (1 species) and chrysophyceae (1species). The zooplankton presence was 5 species (3 classes) and they were consisted Rotifers (2 species), Cepepoda (2species) and Branchiopoda (1 species). Water quality parameter values were as follow: temperature 27-30 0C, transparency 24-32 cm, pH 5, current speed 0.33-0.43 m/s, DO 4.36-5.12 mg/L, CO2 10.64-13.98 mg/L, nitrat 0.22-0.42 mg/L, phosphate 0.18-0.20 mg/L. The number of the plankton presence indicates that water in the upstream of the Siak River can be categorized as oligotrophic. Keywords: Phytoplankton, zooplankton, plankton population,  oligotrophic water         quality